المسئولية الدولية عن جرائم الأسلحة المستقلة ذاتية التشغيل - حسن، خالد عبدالعال إسماعيل (الجامعة البريطانية - كلية القانون, 2022)
أثار التطور التكنولوجي والتقني المتمثل في الذكاء الاصطناعي العديد من المزايا في جميع المجالات المختلفة الطبية والصناعية والإدارية، إلا أنه أصبح في ذات الوقت يشكل تهديدا للجنس البشري وخرقا لقواعد وأحكام القانون الدولي الإنساني وذلك عندما تم إدخال تلك التكنولوجية الحديثة في مجال الأسلحة العسكرية التي أثارت العديد من التعقيدات والمخاطر في مجال النزعات المسلحة. فالواقع يشير إلى بدء الدول المتقدمة مؤخرا في تطوير وإدخال التقنيات التكنولوجية الحديثة وخوارزميات الذكاء الاصطناعي في عملية صنع الأسلحة العسكرية، الأمر الذي تمخض عنه ظهور أنواع جديدة من الأسلحة عرفت باسم الأسلحة المستقلة ذاتية التشغيل أو الروبوتات الفتاكة. هنا بدأ القلق الدولي حول البدء في استخدام تلك الأسلحة (الروبوتات القاتلة) التي يمكنها القتل والتدمير والقيام بالعمليات العسكرية بذاتها دون أي توجيه بشري، وعدم قدرتها على التمييز بين المدنيين والعسكريين، كذلك عدم قدرتها على الامتثال لقواعد القانون الدولي الإنساني. وعليه جاءت فكرة هذا البحث لدراسة مدى مسئولية الدولة عن الجرائم الحادثة بواسطة تلك الأسلحة في ضوء قواعد القانون الدولي العام، وتحديد المسئول عن الجرائم الحادثة بواسطة تلك الأسلحة ذلك في ضوء حداثة ظهور تلك الأسلحة بالإضافة إلى خلو المصادر الاتفاقية والتعاهدية الدولية من أي إطار تنظيمي يبين مدى مسئولية الدولة عن استخدام تلك الأسلحة من عدمه، كذلك الرغبة حول ضمان حماية قانونية لأفراد النزاعات المسلحة من المدنيين والمقاتلين من خطورة استخدام تلك الأسلحة. The technological and technical development of artificial intelligence has raised many advantages in all different medical, industrial and administrative fields, but at the same time, it has become a threat to the human race and a violation of the rules and provisions of international humanitarian law, when this modern technology was introduced in the field of military weapons, which raised many of the complexities and risks in the field of armed conflicts. The reality indicates that developed countries have recently begun to develop and introduce modern technologies and artificial intelligence algorithms in the process of making military weapons, which has resulted in the emergence of new types of weapons known as autonomous weapons or lethal robots. Here, international concerns started around the usage of such weapons (killer robots) that can kill, destroy, and carry out military operations by themselves without any human guidance, and their inability to distinguish between civilians and soldiers, as well as their inability to comply with the rules of international humanitarian law. Accordingly, the idea of this research came to study the extent of the state’s responsibility for the crimes committed by these weapons in the light of the rules of public international law, and to determine who is responsible for the crimes committed by these weapons, in light of the recent emergence of these weapons, in addition to the absence of the international convention and treaty sources from any regulatory framework that shows the extent of the state’s responsibility for the use of these weapons or not, as well as the desire to ensure legal protection for members of armed conflict, civilians and combatants, from the danger of using these weapons.
Keywords: الذكاء الاصطناعي -- المواثيق والمعاهدات الدولية -- المسئولية الدولية -- جرائم الأسلحة المستقلة -- القانون الدولي العام